Cerebral Infarction as the Primary Presentation of Acute Aortic Dissection - Li-Ping Zhou; Xiang-Min Li; Guo-Qing Huang; Fang-Jie Zhang (Reviews in Cardiovascular Medicine, 2023)
Background: The aim of this study was to determine the clinical characteristics and outcome of patients with aortic dissection (AD) who present with an initial manifestation of cerebral infarction. Methods: We retrospectively analyzed patients who were diagnosed with AD and admitted to the emergency department from May 1, 2017 to May 1, 2022. Data was collected for variables including age, sex, clinical manifestation, past medical history, and laboratory test results. Results: Twenty-five patients (2.61%, 22 type A and 3 type B) showed cerebral infarction as the primary presentation for acute AD, while another 933 AD patients (471 type A and 462 type B) who presented with other symptoms served as the control group. Eighteen of the 25 patients (72%) were initially diagnosed with stroke, and the diagnosis of AD was missed. However, patients with a missed diagnosis of AD did not have significantly different mortality to those in whom AD was diagnosed (chi-square test, p > 0.9999). Patients with cerebral infarction as the first presentation had a higher incidence of type A AD than the control patients (p = 0.0002), while their mortality rate was also higher than the control group of AD patients (p < 0.0001). Furthermore, patients with cerebral infarction as the first presentation were more likely to have multiple organ dysfunction. Conclusions: AD with an initial presentation of cerebral infarction is a rare condition with high mortality. However, the initial failure to diagnose AD does not further increase patient mortality.